Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work and Social Computing 2017
DOI: 10.1145/2998181.2998275
|View full text |Cite
|
Sign up to set email alerts
|

Going Gray, Failure to Hire, and the Ick Factor

Abstract: Ageism is a pervasive, and often invisible, form of discrimination. Though it can affect people of all ages, older adults in particular face age-related stereotypes and bias in their everyday lives. In this paper, we describe the ways in which older bloggers articulate a collective narrative on ageism as it appears in their lives, develop a community with anti-ageist interests, and discuss strategies to navigate and change societal views and institutions. Bloggers criticize stereotypical notions that focus exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…For the aforementioned reasons, we re-coded the data specifically to find further instances of respondents' discussing their identity as disabled people or activists in relation to the Disability March. Our codebook was developed based on identity theory literature [42], which has been used in HCI work about older adults use of technology against ageism [29]. Three members of our research team independently coded one interview to identify relevant concepts from identity theory.…”
Section: Methodsmentioning
confidence: 99%
“…For the aforementioned reasons, we re-coded the data specifically to find further instances of respondents' discussing their identity as disabled people or activists in relation to the Disability March. Our codebook was developed based on identity theory literature [42], which has been used in HCI work about older adults use of technology against ageism [29]. Three members of our research team independently coded one interview to identify relevant concepts from identity theory.…”
Section: Methodsmentioning
confidence: 99%
“…However, this perception is changing and a more differentiated view of later life is increasingly supported through movements within the field. This includes research that highlights diversity in later life [25,28,33,42].…”
Section: Digital Participation In Later Lifementioning
confidence: 99%
“…Anne Marie Piper has shown that older adults can find value in online participation through blogging as meaningful engagement in retirement [1] and as a way to push back against issues of ageism [8]. Her work argues for designing technologies to support late-life development and self-expression, focusing on what technologies can contribute to the broader lived experience of older adulthood.…”
Section: Organizersmentioning
confidence: 99%